A new species of Solanum L.(Solanaceae) from Baghdad city Iraq (Baghdad Science Journal, 2015)
Solanum americanum is a new annual shrubby plant seen recently in fields and gardens of Baghdad city. A new species is described and illustrated, inhabit wet or semi dry places and have consequently a mesophytic habit. A detailed morphological study of the stems, leaves, Inflorescence, flower, male and female reproductive organs and fruits has been done, revealed several interesting taxonomic characteristics, which have not previously been studied in Iraq. Also, anatomical studies reveals constant taxonomical characteristics such as the presence of anthocayanine in outer row of epidermis, distinct chlorenchyma in whole cortex, the wide pith of stems, and presence of distinct mesophyll that differentiated into palisade layer and spongy layer in leaves, amphistomatic bearing anomocytic stomatal complexes that are significant and constant characteristics in species studied.